Mitochondrial dual-coding genes in Trypanosoma brucei. - Laura E Kirby; Donna Koslowsky (Public Library of Science (PLoS), 2017)
Trypanosoma brucei is transmitted between mammalian hosts by the tsetse fly. In the mammal, they are exclusively extracellular, continuously replicating within the bloodstream. During this stage, the mitochondrion lacks a functional electron transport chain (ETC). Successful transition to the fly, requires activation of the ETC and ATP synthesis via oxidative phosphorylation. This life cycle leads to a major problem: in the bloodstream, the mitochondrial genes are not under selection and are subject to genetic drift that endangers their integrity. Exacerbating this, T. brucei undergoes repeated population bottlenecks as they evade the host immune system that would create additional forces of genetic drift. These parasites possess several unique genetic features, including RNA editing of mitochondrial transcripts. RNA editing creates open reading frames by the guided insertion and deletion of U-residues within the mRNA. A major question in the field has been why this metabolically expensive system of RNA editing would evolve and persist. Here, we show that many of the edited mRNAs can alter the choice of start codon and the open reading frame by alternative editing of the 5' end. Analyses of mutational bias indicate that six of the mitochondrial genes may be dual-coding and that RNA editing allows access to both reading frames. We hypothesize that dual-coding genes can protect genetic information by essentially hiding a non-selected gene within one that remains under selection. Thus, the complex RNA editing system found in the mitochondria of trypanosomes provides a unique molecular strategy to combat genetic drift in non-selective conditions.